Pyogenic spondylodiscitis: An overview - G.S. Skaf; N.T. Domloj; M.G. Fehlings; C.H. Bouclaous; A.S. Sabbagh; Z.A. Kanafani; S.S. Kanj (Elsevier, 2010)
Summary: Although uncommon, spontaneous and postoperative pyogenic spondylodiscitis entail major morbidity and may be associated with serious long-term sequelae. A review of the literature was done to advance our understanding of the diagnosis, treatment, and outcome of these infections.The principles of conservative treatment are to establish an accurate microbiological diagnosis, treat with appropriate antibiotics, immobilize the spine, and closely monitor for spinal instability and neurological deterioration. The purpose of surgical treatment is to obtain multiple intraoperative cultures of bone and soft tissue, perform a thorough debridement of infected tissue and decompression of neural structures, and reconstruct the unstable spinal column with bone graft with or without concomitant instrumentation. Appropriate management requires aggressive medical treatment and, at times, surgical interventions. If recognized early and treated appropriately, a full recovery can often be expected. Therefore, clinicians should be aware of the clinical presentation of such infections to improve patient outcome. Keywords: Spine, Vertebral osteomyelitis, Spinal discitis, Treatment